Erygowanie i początki funkcjonowania Papieskiego Kolegium Polskiego w Rzymie w XIX w. - Stępień, Marek (Prawo Kanoniczne, 2010)
In the middle of the XIX century the Ressurectionist Fathers started the effort to create the college for the candidates preparing for the ministry (priesthood). Not forgetting about convincing the Pope to this initiative the funds were gathered. The Princess Zofia Odescalchi contributed greatly to this project and founded many grants for Polish alumns studying in the college. Together with the Count Włodzimierz Czacki she solicited in the Apostolic See for creating the college. The project, however, encountered many obstacles because of the lack of funds as well as the strong diplomatic opposition from the Russian and Prussian side. In spite of the diplomatic efforts especially in Russia, which opposed of the establishment of the college, in May 1865 the Pope ordered to create the Pontifical Committee for creating Polish College. In the same time cardinal Antonelli, Secretary of state of the Apostolic See, signed the nomination decrees of the members of the Committee. The president of the Committee became the cardinal Mikołaj Paracciani Clarelli. The Pope Pius IX strongly supported this initiative and with decree from 9 March 1866 Polish Pontifical College was established in Rome, nominating the previous day Priest Peter Semeneka the First Rector of the College. The Statute of the College was confidential, approved and divided into ten articles. The Polish Pontifical College, acting under the auspices of the Pope, was destined to educate young Polish people in the scope of philosophy, theology, the canonical law as well as preparing them for priestly ordinations. At cardinal vice-rector’s request the rector of the college was nominated by the Pope. The formal opening of the college was at 24 March 1866 and the next day six alumns started studying in the college. Among them was Józef Sebastian Pelczar, later the Bishop of Przemyśl beatified and canonized by the Pope John Paul II. The Polish Pontifical College has been functioning continuously since more than hundred and forty years.